How reversible are the effects of silver nanoparticles on macrophages? A proteomic-instructed view. Issue 10 (20th September 2019) - Dalzon, Bastien; Torres, Anaelle; Diemer, Hélène; Ravanel, Stéphane; Collin-Faure, Véronique; Pernet-Gallay, Karin; Jouneau, Pierre-Henri; Bourguignon, Jacques; Cianférani, Sarah; Carrière, Marie; Aude-Garcia, Catherine; Rabilloud, Thierry
Abstract : Silver nanoparticles are known to have profounds effects on living cells, but little is known on how and to which extent cells recover after an acute exposure to silver nanoparticles. This is studied on macrophages in this work. Abstract : Silver nanoparticles are known to strongly affect biological systems, and numerous toxicological studies have investigated their effects. Most of these studies examine the effects immediately following acute exposure. In this work, we have conducted further investigation by studying not only the acute, post-exposure response, but also the cellular response after a 72 hour-recovery-phase post exposure. As a biological model we have used macrophages, which are very important cells with respect to their role in the immune response to particulate materials. To investigate the response of macrophages to nanoparticles and their recovery post exposure, we have used a combination of proteomics and targeted experiments. These experiments provided evidence that the cellular reaction to nanoparticles, including the reaction during the recovery phase, is a very active process involving massive energy consumption. Pathways such as the oxidative stress response, central and lipid metabolism, protein production and quality control are strongly modulated during the cellular response to nanoparticles, and restoration of basic cellular homeostasis occurs during the recovery period. However, some specialized macrophage functions, such as lipopolysaccharide-induced cytokine and nitric oxide production, did not return to their basal levels even 72 hours post exposure, showing that some effects of silver nanoparticles persist even after exposure has ceased.